Grammatical Error Analysis in EFL Student Writing: A Case Study at Universitas Pamulang (Universitas Pamulang, 2025)
The purpose of the study is to find out the types of errors made by students in writing an English paragraph and to find out the types of errors that are generally made by these students. Grammatical error analysis is the analysis of errors in sorting out the right word with the desired meaning in the position or position of the sentence. The research used descriptive qualitative approach with analysis method. Data collection techniques used observation and measurement. Data collection tools used observation sheets and written tests. The analysis results found will be classified in the matrix: (1) syntax category and surface strategy, in the form of errors in noun phrase, verb phrase, transformation, and miscellanous. Then in the surface category, the types of errors that may be found are usually omission errors, additions, form errors, sequence errors, and substitutions. The most dominant syntactic error in students' writing is the error in noun phrase; and (2) in the communicative taxonomy category, the data taken is the result of the first semester English literature students' paragraph writing task. By knowing the types of grammatical errors, it can be used as a reference in providing materials and explanations and also knowing the difficulties that must be corrected immediately. The grammatical errors observed in the student writing tasks are indicative of typical interlanguage phenomena in foreign language acquisition. They highlight specific areas where English rules diverge from the learners' presumed L1, as well as the inherent complexities of mastering English's intricate verb system, article usage, and idiomatic expressions